Seroprevalence and risk factors of hepatitis A virus infection in Zakho City, Kurdistan region, Iraq: A population-based study - Hussein, Nawfal; Naqid, Ibrahim; Abozait, Halder J; Jamal, Shakir; Albrifkani, Delovan; Ahmed, Mateen; Abdullah, Passar; Sharif, Amed; Yasin, Sarbast; Miho, Siaband; Saeed, Awin; Yousif, Yousif; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Hepatitis A virus (HAV) is a major cause of acute hepatitis globally, with higher burden in low- and middle-income countries. Iraq is considered hyperendemic, yet limited regional data are available, particularly from Zakho city. This study aimed to evaluate the seroprevalence of HAV and identify associated risk factors in the general population of Zakho. Methods: A cross-sectional study was conducted in Zakho from February 1 to March 1, 2025. A multistage random sampling approach was used to select 391 participants. Information was collected through structured self-administered questionnaires, and blood samples were tested for HAV IgG. Results: The average age of participants was 33.53 ±13.34 years; 65% were male, and 93.9% lived in urban areas. The overall HAV seroprevalence was 34.5%, with the highest rates found in individuals aged 20–29. No significant associations were found concerning gender (p = 0.772), age (p = 0.095), or water source (p = 0.295). However, handwashing habits were significantly related to HAV status (p = 0.026). Conclusions: The lower HAV prevalence in Zakho compared to national statistics indicates improvements in sanitation and hygiene. Nevertheless, proper hand hygiene remains critical, underscoring the importance of targeted public health education.